Effects of interface states and series resistance on electrical properties of Al/nanostructure CdO/p-GaAs diode - Tascioglu, Ilke; Soylu, Murat; Altindal, Semsettin; Al-Ghamdi, A. A.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2012)
The nanostructure CdO thin film was grown on p-GaAs substrate by the sol-gel method. Electrical characterization of Al/CdO/p-GaAs diode was performed using current-voltage and capacitance-conductance-voltage measurements. The ideality factor and barrier height values of the diode were obtained to be 2.29 and 0.62 eV, respectively. The energy distribution profiles of interface states were determined by means of Hill-Coleman method. The obtained results revealed that the series resistance and interface states have an important effect on electrical characteristics of Al/CdO/p-GaAs diode. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Au/CdO/p-GaAs diode; Density of interface states; Series resistance